Natural Disinfectant Emulgel Associated with Antimicrobial Photodynamic Therapy for Prevention Bovine Mastitis - Bispo, A. S.; de Paula, G.; da Silva, J. B.; Balbinot, R. B.; Nakamura, C.; da Silva Junior, R. C.; Bragatto, J. M.; Caetano, W.; Pozza, M. S. S. (Tropical Animal Science Journal, 2025)
Conventionally, disinfectants based on iodine, hypochlorite, or lactic acid are used in post-dipping for teat hygiene on dairy farms. As a natural alternative for the prevention of bovine mastitis, jurema-preta (Mimosa tenuiflora), copaiba oil (Copaifera martii), and Chlorella vulgaris have antimicrobial and anti-inflammatory properties. Associated with antimicrobial photodynamic therapy (PDT), these substances inhibit Staphylococcus aureus. This study developed two natural emulgels containing these extracts and evaluated their stability, bioadhesiveness, texture, and cytotoxicity for post-dipping to prevent mastitis. The emulgel was developed using Carbopol 934 P (0.25% w/w), jurema extract (12.5% w/w), and Chlorella extract (0.2% w/w), which was dissolved in copaiba oil (4% w/w). Twelve Holstein and Jersey cows were treated with: T1 - control with the use of iodine, T2 - application of emulgel with black jurema and copaiba oil without lighting, and T3 - application of emulgel with black jurema, copaiba oil, and C. vulgaris with lighting. The data obtained in vitro and in vivo were submitted to analysis of variance. For the texture parameters of the emulgel, the formulations showed stability, pseudoplastic behavior, and elastic nature, with no cytotoxic effect. The in vitro study showed that the treatments using light were effective in reducing S. aureus and the extracts were also effective in breaking up pre-formed biofilm by this bacterium. In the in vivo test, there was no significant difference between treatments for somatic cell counts and Staphylococcus in milk and teat swabs. The emugel has antimicrobial potential and can replace iodine for use as post-dipping without cytotoxic effects.